Giving Voice to the Silenced: Using Critical Discourse Analysis to Inform Crisis Communication Theory - Dunn, Carolyn (Journal of business ethics, 2015)
Research exists on how a corporation communicates during a crisis, the impact on its reputation, and how well it weathers that crisis. However, crisis communication research tends to view a company’s communication efforts from the standpoint of success or failure; looking at the communication critically to determine if the company’s power influences or silences potentially alternative voices and viewpoints is not currently part of the discussion. This article argues that critical discourse analysis techniques be added to the framework of crisis communication theory in an effort to ensure that the corporation’s message or position of power does not unfairly marginalize or altogether silence alternative discourses.